Penerapan Customer Relationship Management (CRM) Berbasis Web (Studi Kasus Pada Sistem Informasi Pemasaran di Toko YEN-YEN) - Ovi Dyantina; Mira Afrina; Ali Ibrahim (Jurnal Sistem Informasi, 2012)
CRM is a marketing strategy to create and mantain a good relationship with customer and decrease the possibility customer move away to other competitors. This papers present an analysis of web-based CRM development in Marketing Information System at Toko YEN-YEN. The result is an e-CRM web-based system which can manage customer data, product promotion, product sales data and managing of customer service that used to save customer question and complain to create good relationship with customer. This application, Toko YEN-YEN is expected to mantain good relationship with customer or get new customer, which eventually bring benefits to the company.Key words: Customer Relationship Management, Marketing Information System, E-CRM, Web